Mirror Visual Feedback Prior to Robot-Assisted Training Facilitates Rehabilitation After Stroke: A Randomized Controlled Study - Rong, Jifeng; Ding, Li; Xiong, Li; Zhang, Wen; Wang, Weining; Deng, Meikui; Wang, Yana; Chen, Zhen; Jia, Jie (Frontiers in Neurology, 2021)
Purpose: Robot-assisted training has been widely used in neurorehabilitation, but its effect on facilitating recovery after stroke remains controversial. One possible reason might be lacking consideration of embodiment in robotic systems. Mirror visual feedback is an ideal method to approach embodiment. Thus, we hypothesized that mirror visual feedback priming with subsequent robot-assisted training might provide additional treatment benefits in rehabilitation. Method: This is a prospective, assessor-blinded, randomized, controlled study. Forty subacute stroke patients were randomly assigned into experimental group (N = 20) or control group (N = 20), which received mirror visual feedback or sham- mirror visual feedback prior to robot-assisted training respectively, for 1.5 h/day and 5 days/week for 4 weeks. Before and after intervention, the Fugl-Meyer Assessment Upper Limb subscale, the Functional Independence Measure, the modified Barthel Index, and grip strength were measured. Besides, scores of four specified games were recorded pre and post one-time mirror visual feedback priming before intervention in the experimental group. Results: All measurements improved significantly for both groups following intervention. The Fugl-Meyer Assessment Upper Limb subscale and selfcare subscale of the Functional Independence Measure were improved significantly in the experimental group compared with the control group. A tendency of stronger grip strength was also observed in the experimental group. Moreover, significantly higher scores of two games were revealed after priming. Conclusions: Mirror visual feedback prior to robot-assisted training could prompt motor recovery, increase ability of selfcare, and potentially enhance grip strength in stroke patients, comparing to control treatment. Moreover, mirror visual feedback priming might have the capability to improve patient’s performance and engagement during robot-assisted training, which could prompt the design and development of robotic systems.